Efeitos de choques de temperatura sobre o crescimento, meio ambiente e bem-estar - Pacheco, Bruno Aragão (2021)
The present work aims to verify the effects of a temperature shock on growth, environmental conservation and well-being, under different environmental conditions, of the use of natural resources and climatic dynamics. A general equilibrium model was built which, in addition to considering temperature effects on the production of the economy and the renewal of natural resources, also incorporates the effects of the use of natural resources on production and the impacts of environmental conservation on well-being. The results indicate that greater damage to welfare is associated with greater persistence of the temperature shock, with the lowest maximum capacity of renewable natural resources and with the greatest environmental awareness, which is defined as a greater effects in welfare level of the conservation of natural resources.